Keterkaitan Konsep Tawakal dalam Islam dan Filsafat Stoikisme: Sebuah Analisis Implementatif - Pambudi, Muhammad Sidiq; Matsania, Sab’ati Mela; Fathony, Bimba Valid (Canonia Religia, 2025)
The complexity of modern life has generated profound psychological, social, and spiritual pressures that require a multidisciplinary response. This article analyzes the interrelation between the Islamic concept of tawakal and the philosophy of Stoicism, focusing on both their conceptual foundations and practical implications. Using a literature review method, the study examines relevant books, scholarly articles, and academic works. The findings reveal significant intersections between tawakal and Stoicism, particularly in the principles of self-control, acceptance of what lies beyond human power, and cultivating composure in the face of adversity. While tawakkul is grounded in theological submission to God and Stoicism in rationality and virtue, both can be integrated into a spiritual-philosophical framework that strengthens personal resilience. This study introduces the notion of the “Stoic Muslim” as an integrative model that combines maximum effort, spiritual surrender, and rational emotional regulation. The primary contribution of this research lies in advancing multidisciplinary Islamic scholarship by creating a dialogue between Islamic theology, Western philosophy, and modern psychology. Nevertheless, the study remains limited due to its reliance on theoretical analysis without empirical validation. Future research is recommended to employ qualitative or quantitative methods—such as case studies, in-depth interviews, or psychological surveys—to test the applicability of integrating tawakal and Stoicism in contemporary contexts. Such an approach may provide a more practical framework for enhancing spirituality and psychological resilience in addressing the challenges of modern life.